TRANSFORMATIONAL LEADERSHIP OF SCHOOL PRINCIPALS IN IMPROVING THE PERFORMANCE OF ISLAMIC RELIGIUS EDUCATION TEACHERS IN THE ERA OF SOCIETY 5.0 DI MAN 2 TRENGGALEK - Widiyanti, Arista Ika (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study aims to analyze the transformational leadership of school principals in improving the performance of Islamic Religious Education (PAI) teachers in the era of Society 5.0 in MAN 2 TRENGGALEK by integrating the values of Islamic education management. The approach used is qualitative with a case study design at MAN 2 TRENGGALEK Indonesia. The subjects of the study include school principals, PAI teachers, vice principals for curriculum, and madrasah supervisors. Data were collected through in-depth interviews, participatory observations, and documentation studies, then analyzed using the Miles, Huberman, and Saldaña models with cross-case analysis. The results of the study show that madrasah heads implement integrated management functions including participatory planning, effective organization, implementation of Islamic value-based programs, and structured supervision. PAI teachers at MAN 2 TRENGGALEK play a strategic role in supporting education management through curriculum planning, fostering religious activities, and monitoring the development of students' morals. Collaboration between madrasah heads and PAI teachers has been proven to form a conducive religious climate, strengthen academic achievements, and internalize Islamic values in all aspects of education. The integration of transformational leadership theory with Islamic educational management principles results in relevant leadership models to address the challenges of Society 5.0 without neglecting the roots of traditional values. These findings provide a theoretical contribution to the literature on Islamic education management and practical implications for the development of policies to improve the quality of religious education in Islamic-based schools.